Change on Strategic Planning and Impact on Practice of Control Systems Management - Eka Ananta Sidharta (Jurnal Ilmiah ESAI, 2013)
The business environment that is more complex, turbulent and globalization oriented demand the organization to be a ‘smart’ one. The decision of organization’s strategic, tactical, and operating objectives really direct the going concern entity unit business. The long term strategy measured and objective that reflecting from the mission, will implement well if the management control could set it appropriately and influence company’s performance. The function of the management control system is to ensure that the company’s objective that has been decided by the top management based on the mission and vision of the company can be implemented well by all of the organization members on the entire organization structure (Sidharta, 2011). The objective of this research was to analyze the changing process of management control system precede the ownership changing. The frame work of this research was institutional theory. That theory was the primary theory used to study management accounting. PT Semen Gresik had been chosen as the object with an interpretive research paradigm and a case study phenomenology research method. This research resulted that (1) the changing in management control system process was caused by the change in company management (2) the long term plan was made by high accuracy and rationality, and (3) the changing in management control system effect significantly to the enhancement of company performance.Keyword: management control system, phenomenology qualitative research, institutional Theory, change.